The Role of UMKM in the Community Economy After the Covid-19 Pandemic - Vera Maria; Fatika Andaristi; Nuzulan Nijmah Azzahra (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is that researchers want to analyze and examine the role of Micro, Small and Medium Enterprises (UMKM) in the community's economy before the pandemic, during the pandemic, and after the Covid-19 pandemic with several UMKM owners around Sultan Ageng Tirtayasa University. Then the researcher wants to know whether the economy of some of these UMKM owners remains stable, increasing or vice versa, namely declining. The research method used is a qualitative method using a descriptive and interview approach. The results of this study show that from the sources we got, UMKM owners in the post-Covid-19 pandemic said that their economy has begun to recover but the benefits they get are not as good as before the Covid-19 pandemic